El extraño caso del Dr. Jekyll y Mr. Hyde - Stevenson, Robert Louis, 1850-1894 (Colección Biblioteca nueva de aventuras, 2013)
Dr. Jekyll invented a drug that would change him into the ominous Mr. Hyde. His evil nature, however, became the stronger part of him and to his horror, he no longer needed the formula to transform his appearance.